Comprehensive stress echocardiography in hypertrophic cardiomyopathy. (4th February 2022) - Palinkas, ED; Ciampi, Q; Tesic, M; Palinkas, A; Torres, MAR; Djordievic-Dikic, A; Beleslin, B; Sepp, R; Mori, F; Picano, E
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Stress Echo 2020 study group of the Italian Society of Echocardiography and Cardiovascular Imaging Background: Stress echocardiography (SE) in hypertrophic cardiomyopathy (HCM) has more to offer beyond dynamic left ventricular outflow obstruction (LVOTO) to capture the functional heterogeneity of the disease. Objectives: To determine the feasibility of comprehensive SE in HCM. Methods: We prospectively enrolled 235 HCM patients (age = 48 ± 15 years, 113 men) assessed with exercise stress echocardiography (ESE) in 4 centers. ESE modality was semi-supine bicycle in 29 patients in one center, and treadmill in 206 (followed by same-day, same session, adenosine for step D) in another centers. During SE, we assessed stress-induced new regional wall motion abnormalities (RWMA, step A), coronary flow velocity reserve (CFVR) in left anterior descending coronary artery with Doppler (step D) by semi-supine exercise or adenosine, heart rate reserve (peak/rest heart rate) for EKG-based step E, mitral regurgitation (MR) flow for step F, and LVOTO (step G for gradient). A comprehensive SE score was generated from 0 (all parameters normal) to 5 (all abnormal). Results: Technical success rate was 100% for all steps, except step D (80% with semi-supine, 100% with adenosine after treadmill) and F (232/235, 99%). Extra-analysis time was < 3 minutes for steps A + D + E + F + G. Rate of abnormal results ranged from 73% for step E (peak/rest heart rate reserve < 1.80) to 1% for step A (inducible RWMA), with intermediate values for step D (CFVR < 2.0, 44%), step F (at least moderate MR, 32%) and step G (LVOTG > 50 mm Hg, 26%): see figure. SE score was 0 in 14 pts (6%), 1 or 2 in 202 patients (86%) and ≥ 3 in 19 patients (8%). Conclusions: Comprehensive SE is feasible in HCM with single stress (semi-supine exercise) or hybrid treadmill exercise followed by adenosine for step D. Phenotyping of the multiform manifestations of HCM with a personalized functional blueprint is now possible.